Reformulasi Perubahan Data Jenis Kelamin: Integrasi Kepastian Hukum dan Moralitas Islam dalam Administrasi Kependudukan di Indonesia - Nizam, Nabil; Alviani, Fitri Maulina (Tasyri' : Journal of Islamic Law, 2025)
This study highlights how law can no longer be viewed from a single perspective in the era of globalization. Based on Werner Menski's triangular concept of legal pluralism, which combines the moral-ethical-religious, state, and societal perspectives, this research aims to reformulate the regulation of gender status change in the context of civil registration in Indonesia, ensuring greater legal certainty while grounding itself in religious moral considerations. A normative approach is applied in this study. The main findings reveal that the ratio legis of gender status change aims to protect and recognize the personal and legal status of every citizen. However, the relevance to Menski's triangle theory of legal pluralism is not yet fully reflected in the examination of applications at district courts. Hence, a legal reformulation of the Population Administration Law has become an urgent agenda.